If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3d + 6 = 4d Reorder the terms: 6 + 3d = 4d Solving 6 + 3d = 4d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-4d' to each side of the equation. 6 + 3d + -4d = 4d + -4d Combine like terms: 3d + -4d = -1d 6 + -1d = 4d + -4d Combine like terms: 4d + -4d = 0 6 + -1d = 0 Add '-6' to each side of the equation. 6 + -6 + -1d = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1d = 0 + -6 -1d = 0 + -6 Combine like terms: 0 + -6 = -6 -1d = -6 Divide each side by '-1'. d = 6 Simplifying d = 6
| 3x^2=18-3x | | -2(-7x-9)=-108 | | 0.2x+6.5=6.2 | | 1.6k-72=4k-30 | | A-22+4=-2 | | lny-ln(N-y)=kt+C | | -3x(4x+3)=0 | | 10x^2-9=-9x | | 3(-2x-8)=-54 | | 12h-5=-h-3+13h-2 | | 9-5t=0 | | 1.5w+21=17+1.5w | | y+(5-x)=7 | | -3x+18+n=34 | | 80=10-10x | | 3a+26-3a-26= | | 4+6(x+1)=3x+11+2x | | a+(b-c)=0 | | 2(-3-3)=-9 | | S^2+3s=-11 | | 3ln(2x)+1=5 | | 20x+2y=12 | | ln(2x+11)+ln(x-9)-2ln(x)=0 | | 2(-6-3)=-9 | | -6/3=-2 | | 2c+27=5c | | 3a-b-2a+56= | | 2x+3x-3=8 | | .1x+x=3000 | | 9x+45=3(4x-3) | | 5(x-2)+10=5x-25 | | 150a-555= |